LGBTQAI+ books for children and teens : providing a window for all - Dorr, Christina H.; Deskins, Liz (ALA Editions, 2018)
There is a rich and varied body of literature for lesbian, gay, bisexual, transgender, queer/questioning, asexual/allied and intersexed young people, which can function as a mirror for LGBTQAI+ individuals and as a window for others. This resource for librarians who work with children and teens not only surveys the best in LGBTQAI+ lit but, just as importantly, offers guidance on how to share it in ways that encourage understanding and acceptance among parents, school administrators, and the wider community. Helping to fill a gap in serving this population, this guide discusses the path to marriage equality, how LGBTQAI+ terms have changed, and reasons to share LGBTQAI+ literature with all children; presents annotated entries for a cross-section of the best LGBTQAI+ lit and nonfiction for young children, middle year students, and teens, with discussion questions and tips; offers advice on sensitive issues such as starting conversations with young people, outreach to stakeholders, and dealing with objections and censorship head on; and ideas for programming and marketing. This resource gives school librarians, children's, and YA librarians the guidance and tools they need to confidently share these books with the patrons they support.